(untitled) (British Journal of Global Ecology and Sustainable Development, 2026)
This article examines the methodological foundations of the integrative teaching model within the theory of primary education, focusing on its conceptual origins, epistemological premises, and pedagogical implications. Integrative teaching is considered not merely as a didactic technique, but as a holistic educational paradigm that responds to the fragmentation of knowledge and learning experiences in early schooling. The study argues that integration in primary education emerges from the convergence of psychological, pedagogical, and philosophical approaches that emphasize the unity of cognitive, emotional, and social development. Through theoretical analysis and methodological reflection, the article explores how integrative teaching reshapes curriculum design, instructional strategies, and the role of the teacher in facilitating meaningful learning. The findings demonstrate that the integrative model provides a coherent methodological framework for addressing contemporary educational challenges, including competency-based education, interdisciplinary learning, and learner-centered pedagogy. The article concludes that the integrative teaching model represents a critical methodological shift in primary education theory, requiring systematic conceptualization rather than fragmented practical implementation.